ON THE USE OF ANTHROPONYMS IN POETRY - Слободяк, С.І. (SWorldJournal, 2023)
The article deals with the consideration of the anthroponymic structural models of the poetical works of the British authors of the 18th –19th centuries (G. G. Byron, R. Burns, W. Blake, etc.). Special attention is paid to the correlation between the Brit